Pembelajaran Karakter Kreatif Melalui Pendidikan Seni di SD N 04 Bawu Jepara - Nizam, Alif Syahrul; Widyaningrum, Ari; Budiman, Muhammad Arief (STKIP Andi Matappa Pangkep, 2021)
In art education, there is a character value used to achieve students’ competence that is creative. The purpose of the research is to know discipline character’s learning through art education in SDN 04 Bawu Jepara. The type of this research is qualitative research, carried out at SDN 04 Bawu, Batealit District, Jepara Regency, the school year 2019/2020. The source of data in this research are obtained through interviews, evaluation, and documentation. The results of this research are based on observations and interviews with headmaster, teachers and students have carried out the creativity character learning through art education. It can be seen through the students who have done making various kinds of work using creative ideas that they own.